Pengaruh Kompetensi, Komunikasi Interpersonal, dan Disiplin Kerja terhadap Kinerja Karyawan PT Bahtera Bahari Shipyard Batam - Eko Wahyu Cahyono; Sumardin Sumardin; Sabri Sabri (eScience Humanity Journal, 2026)
This study aims to analyze the influence of competence, interpersonal communication, and work discipline on employee performance at PT Bahtera Bahari Shipyard Batam. Human resource quality is a critical factor in determining organizational success, particularly in the shipbuilding industry, where employees are required to demonstrate high levels of technical competence, effective communication, and strong work discipline. This research employed a quantitative approach using a survey method. The population consisted of all employees of PT Bahtera Bahari Shipyard Batam, totaling 78 employees, and a saturated sampling technique was applied, resulting in all employees being selected as respondents. Data were collected through structured questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The findings indicate that competence has a positive and significant effect on employee performance. Interpersonal communication also demonstrates a positive and significant influence on employee performance by enhancing collaboration, understanding, and coordination among employees. Furthermore, work discipline emerges as the most dominant factor affecting employee performance, reflecting the importance of attendance, compliance with regulations, responsibility, and adherence to organizational procedures. Simultaneously, competence, interpersonal communication, and work discipline significantly influence employee performance, explaining 52.7% of the variance in employee performance, while the remaining 47.3% is influenced by other factors outside the model. These findings suggest that organizations should prioritize employee competency development, strengthen communication practices, and foster a culture of discipline to improve overall organizational performance. The study contributes to the human resource management literature by providing empirical evidence from the shipbuilding industry in Indonesia.